FEASIBILITY ANALYSIS OF CIHERANG VARIETY SUPERIOR RICE FARMING IN PARIGI VILLAGE, BAKARANGAN DISTRICT, TAPIN REGENCY - Hana Nurhakimah Ikram; Ana Zuraida; Arief Hidayatullah (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
This study aims to analyze the superior rice farming of the Ciherang variety including the costs, revenues, income, profits, and feasibility of the Ciherang variety superior rice farming in Parigi Village, Bakarangan District, Tapin Regency. This research was conducted in May 2022. The data was collected in the form of primary data and secondary data using the Census sampling method. Analysis of the data used is a qualitative analysis that is processed descriptively and a financial analysis to calculate the cost, revenue, income, profit, and feasibility of Ciherang rice farming. The results showed that the average production was 4.337,5kg/farmer. The average total cost is Rp 11.931.789/farmer, the average revenue is Rp 18.056.250/farmer, the average income is Rp 9.227.469/farmer, and the average profit received by farmers is Rp 6.124.461. The ratio R/C value is 1,53. Thus, the superior rice farming of the Ciherang variety in Parigi Village, Bakarangan District, Tapin Regency is feasible to cultivate.